Shear bond strengths of aged and non-aged CAD/CAM materials after different surface treatments - Kilinc, Hamiyet (J Adv Prosthodont, 2020)
PURPOSE: To assess shear bond strengths (SBS) of resin composites on aged and non-aged prosthetic materials with various surface treatments. MATERIALS AND METHODS: Cerasmart (CE), Vita Enamic (VE), Vita Mark II (VM), and IPS e.max CAD (EC) blocks were sliced, and rectangular-shaped specimens (14 × 12 × 1.5 mm; N = 352) were obtained. Half of the specimens were aged (5000 thermal cycles) for each material. Non-aged and aged specimens were divided into 4 groups according to the surface treatments (control, air abrasion, etching, and laser irradiation; n = 11) and processed for scanning electron microscopy (SEM). The repair procedure was performed after the surface treatments. SBS values and failure types were determined. Obtained data were statistically analyzed (P≤.05). RESULTS: The material type, surface treatment type, and their interactions were found significant with regard to SBS (P<.001). Aging also had a significant effect on prosthetic material-resin composite bonding (P<.001). SBS values of non-aged specimens ranged from 12.16 to 17.91 MPa, while SBS values of aged specimens ranged from 9.46 to 15.61 MPa. Non-aged VM in combination with acid etching presented the highest score while the control group of aged CE showed the lowest. CONCLUSION: Etching was more effective in achieving durable SBS for VM and EC. Laser irradiation could be considered as an alternative surface treatment method to air abrasion for all tested materials. Aging had significant effect on SBS values generated between tested materials and resin composite.